Comparative Visual Analysis of Structure‐Performance Relations in Complex Bulk‐Heterojunction Morphologies. (4th July 2017) - Aboulhassan, A.; Sicat, R.; Baum, D.; Wodo, O.; Hadwiger, M.
Abstract: The structure of Bulk‐Heterojunction (BHJ) materials, the main component of organic photovoltaic solar cells, is very complex, and the relationship between structure and performance is still largely an open question. Overall, there is a wide spectrum of fabrication configurations resulting in different BHJ morphologies and correspondingly different performances. Current state‐of‐the‐art methods for assessing the performance of BHJ morphologies are either based on global quantification of morphological features or simply on visual inspection of the morphology based on experimental imaging. This makes finding optimal BHJ structures very challenging. Moreover, finding the optimal fabrication parameters to get an optimal structure is still an open question. In this paper, we propose a visual analysis framework to help answer these questions through comparative visualization and parameter space exploration for local morphology features. With our approach, we enable scientists to explore multivariate correlations between local features and performance indicators of BHJ morphologies. Our framework is built on shape‐based clustering of local cubical regions of the morphology that we call patches. This enables correlating the features of clusters with intuition‐based performance indicators computed from geometrical and topological features of charge paths.